PENGARUH PROSES PEMBELAJARAN PERKOPERASIAN TERHADAP MINAT BERKOPERASI MAHASISWA PENDIDIKAN EKONOMI KOPERASI - Hari Putra, I Wayan; Matsum, Junaidi H.; Utomo, Bambang Budi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2014)
Abstract: This study aims to determine the effectof the process of cooperation learning on student’s cooperation interest in Economy Cooperation Department of Teacher Trainingand Education Faculty in Tanjungpura University. The method that used wasdescriptive method, while the form of research was the study of relationship.Sample that used in this study was 45 people from cooperation economicseducation students in regular A and regular B who were in 8th semesters that havepassed the cooperations subject, Indonesian cooperations, accountingcooperations, management cooperations, auditing cooperations, and practice andseminar cooperations. The results of the data analysis showed that cooperationlearning in Teacher Training and Education Faculty Tanjungpura University is ingood criteria and student’s cooperation interest in Economy Cooperation Department is in quite good category.Regression test results showed that the effect of process cooperation learninghas a significant impact on student’s cooperation interest in Economycooperation department is 14,4%, while 85.6% is influenced by other variableswhich not included in this study.Keywords: Cooperationlearning process, interest in cooperation, cooperation economics educationstudentsAbstrak: Penelitian ini bertujuan untukmengetahui pengaruh proses pembelajaran perkoperasian terhadap minatberkoperasi mahasiswa pendidikan ekonomi koperasi Fakultas Keguruan dan IlmuPendidikan Universitas Tanjungpura. Metode penelitian yang digunakan adalah metodedeskriptif, sedangkan bentuk penelitian adalah studi hubungan. Sample yangdigunakan dalam penelitian ini adalah 45 orang mahasiswa pendidikan ekonomi koperasireguler A dan reguler B semester 8 yang telah lulus mata kuliah perkoperasian,koperasi Indonesia, akuntansi koperasi, manajemen koperasi, auditing koperasi, danpraktek dan seminar koperasi. Hasil analisis data menunjukan bahwa prosespembelajaran perkoperasian di Fakultas Keguruan dan Ilmu Pendidikan UniversitasTanjungpura masuk dalam kriteria baik dan minat berkoperasi mahasiswapendidikan ekonomi koperasi masuk dalam kategori cukup baik. Hasil uji regresimenunjukan proses pembelajaran perkoperasian mempunyai pengaruh yang signifikanterhadap minat berkoperasi mahasiswa pendidikan ekonomi koperasi sebesar 14,4%,sedangkan 85,6% dipengaruhi oleh variabel lain yang tidak diikutsertakan padapenelitian ini.Katakunci: Proses pembelajaran perkoperasian, minat berkoperasi, mahasiswapendidikan ekonomi koperasi